Death anxiety and psychological distress post-donation in non-directed living kidney donors. Issue 8 (2nd August 2020) - Hamama-Raz, Yaira; Ring, Lia; Mahat-Shamir, Michal; Ben-Ezra, Menachem
Abstract: The current study sought to assess death anxiety and psychological distress among kidney donors, in comparison to a control population. Seventy-eight non-directed living kidney donors were recruited through the Israeli voluntary kidney donation association. This sample was compared to 396 participants from a control population. The results revealed that non-directed living kidney donors had higher levels of death anxiety in comparison to the control population while their psychological distress was lower in comparison to the control population. The results of this study highlight the importance of relating to non-directed living kidney donors' death anxiety.